History of collection and discovery of polychaetes (Annelida), including a bibliography, from the Indo-Malay-Philippines Archipelago and surrounding seas - Glasby, Christopher J; al Hakim, Inayat (Raffles Bulletin of Zoology, 2017)
The polychaetes (Annelida) of Indo-Malay-Philippines Archipelago (IMPA) are poorly known taxonomically as a result of a lack of systematic collections, the dispersed nature of the collections throughout the world, and the lack of knowledge on the whereabouts of the type material. This has hindered both taxonomic studies on the group and, ultimately, biodiversity comparisons with other species-rich marine groups. In this study, we trace the history of scientific discovery of polychaetes and allied forms from IMPA. We find that the polychaetes and allies of the IMPA are described in a vast literature spanning almost 300 years, covering three main periods: shore collecting by the first European colonisers during the seventeenth to end of the nineteenth centuries, deep-sea collections from nineteenth and twentieth century European voyages of discovery, and post-1960s bilateral and multinational collaborative voyages and expeditions. A comprehensive bibliography of relevant literature is produced and the fate of the polychaete specimens collected discussed
World Polychaeta Database (WPolyD).